Strategi Pengembangan Fungsi Balai Benih Ikan (BBI) Dalam Penyediaan Benih Ikan Berkualitas Di Kabupaten Ciamis - Yanti Herayani (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The solutions for the problem of less optimal strategy implementation in BBI Sukamaju need to be found, and as the first step, efforts are needed to evaluate the chosen strategy, to review and to re-evaluate the situations (strengths, weaknesses, opportunities and business threats), and also to update the formulated strategy so that it suits the developments of the external environment in order to support the efforts of function development of Balai Benih Ikan (BBI) on Dinas Peternakan dan Perikanan Kabupaten Ciamis at Supplying of Quality Fish Seeds in Ciamis Regency. This study explains the steps for choosing the right strategy based on the Routweer concept approach by comparing the performance of the strategy before the new strategy is introduced, which is the development strategy or known by the name Restructurisation. By using a semi-structured interview method, SWOT analysis and QSPM, there will be found an effective strategy that can help achieve the organization’s objectives effectively and efficiently to support the vision, mission and the goals of regional development. From this research, based on QSPM calculation results, it can be concluded that the strategy improves coordination with various work partners (7,8), increases the partnership with UPR to increase the seed production, increases the cooperation with universities, research institutes and other partners (6,25), and becomes a priority strategy.